2D/3D spin crossover porous coordination polymers based on isomeric tetrapyridyl benzene ligands. Issue 19 (28th April 2022) - Wu, Wei-Wei; Ruan, Ze-Yu; Shi, Chen-Guang; Mai, Jin-Tao; Cui, Wen; Ni, Zhao-Ping; Wu, Si-Guo; Tong, Ming-Liang
Abstract : Topology and guest-dependent spin crossover behaviors are revealed in three-dimensional and two-dimensional porous coordination polymers based on the isomeric tetrapyridyl benzene ligands. Abstract : By employing cyanoborohydride and isomeric tetrapyridyl benzene ligands, a new three-dimensional (3D) [Fe(3-tpb)(NCBH3 )2 ] (1 ·2H 2 O, 3-tpb = 1, 2, 4, 5-tetra(pyridin-3-yl)benzene) and a two-dimensional (2D) [Fe(4-tpb)(NCBH3 )2 ] (2 ·2-NapSMe and 2 ·H 2 O·3DMF, 4-tpb = 1, 2, 4, 5-tetra(pyridin-4-yl)benzene, 2-NapSMe = 2-(methylthio)naphthalene) porous coordination polymer (PCP) were synthesized, and exhibited the diamond ( dia ) and square lattice ( sql ) topologies, respectively. Complex 1 ·2H 2 O shows gradual and incomplete spin crossover (SCO) behavior because of the rigid framework and larger octahedral distortion. In contrast, abrupt SCO and hysteretic two-step SCO behaviors are observed in 2 ·2-NapSMe and 2 ·H 2 O·3DMF, respectively. This work proves that the modulation of host–guest interactions significantly influences the transition temperatures and SCO characteristics in a flexible PCP. More importantly, diverse multidentate ligands can be used to construct PCPs with novel topologies and tunable SCO properties.